2022
DOI: 10.1016/j.nefro.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of acute kidney injury in adult patients hospitalized with COVID-19: A systematic review and meta-analysis

Abstract: Antecedentes y objetivo: El conocimiento de la incidencia de lesión renal aguda (LRA) en pacientes con enfermedad por coronavirus 2019 (COVID-19) puede ayudar a los equipos de atención médica a llevar a cabo un plan de atención específico. Este estudio tuvo como objetivo determinar la incidencia de LRA en pacientes hospitalizados con COVID-19. Métodos: La búsqueda electrónica cubrió la investigación publicada hasta el 20 de junio de 2020 e incluyó cinco bases de datos, PubMed, Embase, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…Renal involvement in COVID-19 infection is complex and probably occurs due to several factors, including direct injury to the renal endothelium, tubular epithelium and podocytes [27]; cytokine storm, with the release of several interleukins and cytokines [3]; cardiorenal syndrome, caused by right ventricular dysfunction secondary to pulmonary infection; hypercoagulable statea; and release of nephrotoxic substances such as creatine phosphokinase secondary to rhabdomyolysis [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal involvement in COVID-19 infection is complex and probably occurs due to several factors, including direct injury to the renal endothelium, tubular epithelium and podocytes [27]; cytokine storm, with the release of several interleukins and cytokines [3]; cardiorenal syndrome, caused by right ventricular dysfunction secondary to pulmonary infection; hypercoagulable statea; and release of nephrotoxic substances such as creatine phosphokinase secondary to rhabdomyolysis [2].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AKI among hospitalised patients with COVID-19 has shown to be variable, depending upon the severity of the disease and whether they are outpatient, in the ward or intensive care unit (ICU) environment. A recent systematic review, which included 30 studies and 18,043 patients with COVID-19, observed an overall incidence of AKI of 9.2% (95% confidence interval [CI] 4.6-13.9%), and 32.6% (95% CI 8.5-56.6%) in the ICU [3]. Another systematic review from the beginning of the pandemic included 79 studies and 49,692 patients, and observed a significant variation in the incidence of AKI and kidney replacement therapy (KRT) and the risk of death in patients who develop AKI depending on the continent.…”
Section: Introductionmentioning
confidence: 99%
“…SARS‐CoV‐2 may increase thrombophilia in PNH in the context of multiple triggers, such as increased inflammatory factors, endothelial injury, platelet, and thrombin activations. Acute kidney injury of PNH will be caused by a variety of reasons, such as the direct toxicity of free hemoglobin released by broken red blood cells, the constriction of renal blood vessels caused by NO consumption, and the direct damage caused by the coronavirus and cytokine storm 2,21,22 . In our cohort, there were 5 patients with severe renal function decline (GFR ≤60 mL/min/1.73 m 2 ), even 1 accepted hemodialysis.…”
Section: Discussionmentioning
confidence: 92%
“…11 These results differ from those of some systematic reviews that show a lower incidence and higher mortality particularly in ICU patients worldwide. 12,13 This difference could probably be related to the delayed medical care caused by the saturation of Peruvian hospitals during the first and second waves of the pandemic and the prioritization of ICU admission of patients with better prognosis. 14 Similar to other countries in Latin America, in Peru, hospitalized patients with AKI in need of dialysis most frequently receive hemodialysis (HD) given the little availability of continuous renal replacement therapy (CRRT), prolonged intermittent renal replacement therapy, or peritoneal dialysis (PD) even for critically ill patients.…”
Section: Epidemiology Of Aki In Perumentioning
confidence: 99%